25.2 Вепсский язык в России: Подробный отчет ELDIA - Grünthal, Riho; Puura, Ulriikka; Zajceva, Nina; Karjalainen, Heini
Russian translation of the case-specific report about the study on the Veps language in Russia, conducted within the EU-FP7 research project ELDIA